2019
DOI: 10.20945/2359-3997000000165
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between peak systolic velocity of the inferior thyroid artery and technetium-99m pertechnetate thyroid uptake in differentiating Graves’ disease from thyroiditis

Abstract: Objectives The differentiation between the various etiologies of thyrotoxicosis, including those with hyperthyroidism (especially Graves’ disease [GD], the most common cause of hyperthyroidism) and without hyperthyroidism (like thyroiditis), is an important step in planning specific therapy. Technetium-99m ( 99m Tc) pertechnetate thyroid scanning is the gold standard in differentiating GD from thyroiditis. However, this technique has limited availability, is contraindica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 24 publications
1
5
0
1
Order By: Relevance
“…Further by ROC analysis, we obtained a similar mean PSV in ITA cutoff value of 29.5 cm/sec, at a sensitivity of 91.8% and specificity of 90.9%. A study by Malik et al [ 8 ] showed that measurement of PSV-ITA by CFDU is a good diagnostic approach to discriminate between GD and thyroiditis with a sensitivity of 91% and specificity of 89% to differentiate between the two conditions at a cutoff level of 30 cm/s, which was similar to that obtained in our study. Our results are also in agreement with those of Kurita and cols.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Further by ROC analysis, we obtained a similar mean PSV in ITA cutoff value of 29.5 cm/sec, at a sensitivity of 91.8% and specificity of 90.9%. A study by Malik et al [ 8 ] showed that measurement of PSV-ITA by CFDU is a good diagnostic approach to discriminate between GD and thyroiditis with a sensitivity of 91% and specificity of 89% to differentiate between the two conditions at a cutoff level of 30 cm/s, which was similar to that obtained in our study. Our results are also in agreement with those of Kurita and cols.…”
Section: Discussionsupporting
confidence: 90%
“…We used the Chi-square test for categorical data and the independent samples Student's t test for parametric quantitative data. Based on previous literature a T3/T4 ratio (ng/μg) cutoff of more than 20,[ 3 ] an FT3/FT4 ratio more than 0.3[ 7 ] and a mean PSV-ITA of more than 30 cm/s[ 8 ] were considered as suggestive of GD. In addition, we did an ROC curve analysis to derive cutoffs.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…The study by Malik et al 43 also showed that 99m TC pertechnetate scanning exhibited a similar specificity and a positive predictive value (PPV) as ITA-PSV in differentiating between Graves’ disease and thyroiditis, although a greater sensitivity was encountered with scintigraphy (100% versus 91%, respectively). However, the latter study and a former study by Smith and Oates 46 observed that some patients with resolving thyroiditis can display increased uptake on nuclear scanning that may be indicative of Graves’ disease and this can be potentially confusing.…”
Section: Discussionmentioning
confidence: 90%
“…Another study identified a mean ITA-PSV cut-off value of 30 cm/s for differentiating between Graves’ disease and thyroiditis with a sensitivity of 91% and a specificity of 89% on ROC curve analysis. 43 …”
Section: Discussionmentioning
confidence: 99%
“…La gammagrafía de tiroides es considerada por algunos autores como la prueba de referencia en imágenes para el diagnóstico diferencial de la etiología del hipertiroidismo. Malik, et al ., encontraron una sensibilidad de la captación de tecnecio-99 del 100 %, igual a la sensibilidad de los TRAbs, y una especificidad de 84 % Vs. 89 % 27 . Los datos del presente estudio son similares a los de Perdomo, et al ., quienes no encontraron captación, o solo baja en el 19 %, e hipercaptación, en el 80,5 % de los pacientes con tirotoxicosis 28 .…”
Section: Discussionunclassified